Comprehensive evaluation of the properties of camel bone gelatin: impact of the duration of pre-treatment and extraction - Meriem Imelhayene; Abdelkader Adamou; Samira Becila; Ayad Redjeb; Dahia Saidj; Abdelhakim Senoussi; Dimitris Sarris; Eleni Naziri (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux)
Background: The growing interest in innovative uses for slaughter by-products from camels could generate added value from this multipurpose animal. Aim: This study investigates the extraction of gelatin from camel bones, discusses its potential as a novel protein source and assesses how its properties are affected by the duration of the pre-treatment and extraction processes. Methods: Four bone samples from 4-4.5-year-old male Sahraoui camels were utilized. The gelatin extraction process comprised demineralization with hydrochloric acid, followed by pre-treatment with sodium hydroxide for 24 or 48 hours and subsequent chemo-thermal extraction in acetic acid for 6 or 12 hours. Results: Physicochemical, microscopic and functional properties of the extracted gelatin were evaluated. Gelatin yields varied from 15.65% ± 0.15 to 21.85% ± 0.25. Variations were attributed to the combined duration of pre-treatment and chemo-thermal extraction. Extended processing times increased structural degradation. The elemental analysis revealed a stable carbon and oxygen content. The variable nitrogen levels revealed a positive correlation with extraction intensity. The gelatin pH values exhibited little variation, ranging from 4.66 to 4.91. The gelatin demonstrated interesting functional properties, including a high water holding capacity of 1080 ± 4.24%, a fat binding capacity of 880 ± 98.99%, and a Bloom value of 317.96 ± 8.51 g. These characteristics were predominantly influenced by the length of pre-treatment and extraction. Optimal results were obtained under moderate processing conditions. Conclusions: Camel bone gelatin has physicochemical and functional characteristics, including a high water holding capacity, a high fat binding capacity and a favorable Bloom value, which make it a valuable candidate for various industrial applications.